The Gendering of Objectivity and Resistance to Feminist Knowledge: An Interview with Anne Fausto-Sterling and Julie Nelson - Lodahl, Mads Ananda; Skewes, Lea (Kvinder, Køn & Forskning, 2021)
Editorial note: In our interview with Anne Fausto-Sterling and Julie Nelson, ”The Gendering of Objectivity and Resistance to Feminist Knowledge”, we would like to correct an error on Anne Fausto-Sterling’s request. In the discussion about Hubert Humphrey, it was not he who spoke about women leaders, but his physician – the white House doctor.